Role Playing in Consumer Protection Law: The Market Day Project - Samantha Hardy (Legal Education Review)
[Extract] Following the March 2004 annual meeting of the National People’s Congress in China, the country’s Parliament formally approved 13 constitutional amendments, including some that addressed the issues of private property ownership and human rights.1 These amendments contain radical changes to the underlying legal framework that regulates life in China. The notion of private property ownership, whilst familiar to most developed and, indeed, many developing countries, represents a significant departure from the system of law that emerged as a result of the rise to power of the Communist Party in the 1940s. Despite ongoing debate about the nature of human rights and arguments of cultural relativism, the ongoing incorporation of basic international human rights standards into the domestic law of countries throughout the world highlights the increasingly “global” nature of many important issues.